The wide-field, multiplexed, spectroscopic facility WEAVE: survey design, overview, and simulated implementation - Jin, Shoko; Xylakis-Dornbusch, Theodora (Monthly notices of the Royal Astronomical Society, 2024)
WEAVE, the new wide-field, massively multiplexed spectroscopic survey facility for the William Herschel Telescope, saw first light in late 2022. WEAVE comprises a new 2-deg field-of-view prime-focus corrector system, a nearly 1000-multiplex fibre positioner, 20 individually deployable ‘mini’ integral field units (IFUs), and a single large IFU. These fibre systems feed a dual-beam spectrograph covering the wavelength range 366-959 nm at R ∼ 5000, or two shorter ranges at $R\sim 20\, 000$. After summarizing the design and implementation of WEAVE and its data systems, we present the organization, science drivers, and design of a five- to seven-year programme of eight individual surveys to: (i) study our Galaxy’s origins by completing Gaia’s phase-space information, providing metallicities to its limiting magnitude for ∼3 million stars and detailed abundances for ∼1.5 million brighter field and open-cluster stars; (ii) survey ∼0.4 million Galactic-plane OBA stars, young stellar objects, and nearby gas to understand the evolution of young stars and their environments; (iii) perform an extensive spectral survey of white dwarfs; (iv) survey ∼400 neutral-hydrogen-selected galaxies with the IFUs; (v) study properties and kinematics of stellar populations and ionized gas in z < 0.5 cluster galaxies; (vi) survey stellar populations and kinematics in ${\sim} 25\, 000$ field galaxies at 0.3 ≲ z ≲ 0.7; (vii) study the cosmic evolution of accretion and star formation using >1 million spectra of LOFAR-selected radio sources; and (viii) trace structures using intergalactic/circumgalactic gas at z > 2. Finally, we describe the WEAVE Operational Rehearsals using the WEAVE Simulator.
Veröffentlicht: 11 March 2023
Gesehen am 16.05.2025